Filth - Irvine Welsh (London Vintage, 1998)
With the Christmas season upon him, Detective Sergeant Bruce Robertson of Edinburgh's finest is gearing up socially-kicking things off with a week of sex and drugs in Amsterdam. There are some sizable flies in the ointment, though: a missing wife and child, a nagging cocaine habit, some painful below-the-belt eczema, and a string of demanding extramarital affairs. The last thing Robertson needs is a messy, racially fraught murder, even if it means overtime-and the opportunity to clinch the promotion he craves. Then there's that nutritionally demanding (and psychologically acute) intestinal parasite in his gut. Yes, things are going badly for this utterly corrupt tribune of the law, but in an Irvine Welsh novel nothing is ever so bad that it can't get a whole lot worse. . .
Keywords: Dark; Fiction; Mystery; Thriller